Biotribological performance of medical-grade UHMW polyethylene-based hybrid composite for joint replacement. Issue 9 (November 2021) - Hussain, Omar; Ahmad, Babar; Sheikh, Shahid Saleem
Ultra high molecular weight polyethylene (UHMWPE) is widely used for articulating surfaces in total hip and knee replacements. In the present work, the tribological properties of UHMWPE-based nano composites were studied in order to meet the demands of current bearing applications. UHMWPE matrix reinforced with 0.5, 1, and 2 weight percentage of alumina nano powder were fabricated by hot pressing. The dispersion and microstructure of composite material was established by X-ray diffraction (XRD) and scanning electron microscope (SEM) micrograph. The tests were carried out on a reciprocating sliding pin-on-disc tribometer at human body temperature (37±1 ° C) under dry and human serum lubricating environments for a normal load of 46 N and 52 N, a constant sliding speed of 4 mm. Under these testing conditions, it has been observed that the wear behavior of the developed composites improved with increase in weight percentage of alumina nano powder. The results show that at 52 N load, the maximum value of wear rate was 7.9x10 −7  mm 3 /Nm and the minimum value 1.6x10 −7  mm 3 /Nm was obtained. SEM was used to examine the worn surface and it was observed that human serum adheres to the surface of the composite pins upon sliding, resulting in the formation of a film which results in better wear resistance of the composite pins under human serum lubrication than dry sliding. This study implies that the use of nano alumina power will reduce the wear of UHMWPE based composite under human serum lubrication.